Autoimmune premature ovarian failure - Komorowska, Beata (Menopause Review/Przegląd Menopauzalny, 2016)
Premature ovarian failure (POF), also termed as primary ovarian insufficiency (POI), is a highly heterogenous condition affecting 0.5-3.0% of women in childbearing age. These young women comprise quite a formidable group with unique physical and psychological needs that require special attention. Premature ovarian senescence (POS) in all of its forms evolves insidiously as a basically asymptomatic process, leading to complete loss of ovarian function, and POI/POF diagnoses are currently made at relatively late stages. Well-known and well-documented risk factors exist, and the presence or suspicion of autoimmune disorder should be regarded as an important one. Premature ovarian failure is to some degree predictable in its occurrence and should be considered while encountering young women with loss of menstrual regularity, especially when there is a concomitant dysfunction in the immune system.